Child's buccal cell mitochondrial DNA content modifies the association between heart rate variability and recent air pollution exposure at school. (February 2019) - Saenen, Nelly D.; Provost, Eline B.; Cuypers, Ann; Kicinski, Michal; Pieters, Nicky; Plusquin, Michelle; Vrijens, Karen; De Boever, Patrick; Nawrot, Tim S.
Abstract: Background: Studies investigating short-term exposure to ambient air pollution and heart rate variability (HRV) suggest that particulate matter (PM) exposure is associated with reductions in measures of HRV. Mitochondria are sensitive to PM exposure and may represent a biologically relevant underlying mechanism. However, evidence in children is lacking. Objectives: Here we examine whether PM has an influence on children's HRV and evaluate whether mitochondrial DNA content (mtDNAc) reflects individual susceptibility. Methods: Within a panel study in primary school children (aged 9–12 years), we measured HRV in a subset of 60 children on three different days during school-time using four indicators: normal-to-normal intervals (SDNN), square root of mean squared difference of normal-to-normal intervals (rMSSD), high frequency (HF), and low frequency (LF). This resulted in a total number of 150 visits (median number of visits per child: 2.5/child). MtDNAc was measured using qPCR in buccal cells. We measured recent PM exposure at the school. Residential 24-hour mean exposure to PM was modelled with a high resolution spatial temporal model. Mixed-effects models were used to estimate the association between HRV and recent PM exposure and potential effect-modification by mtDNAc. Results: Children were on average [SD] 9.9 [1.2] years and comprised 39 girls. Median [25th–75th] recent outdoor PM2.5 and PM10 exposure at school was 6.20 [2.8–12.8] μg/m 3 and 29.3 [24.7–42.0] μg/m 3, respectively. In children with low mtDNAc (25th percentile), we observed for each 10 μg/m 3 increment in recent PM2.5 exposure a lowering in the LF parameter with 9.76% (95% CI: −16.9 to −1.99%, p = 0.02; pint  = 0.007). Children with high mtDNAc did not show this association. For PM10 exposure, we observed an inverse association with three HRV indicators in children with low mtDNAc: −2.24% (95% CI: −4.27 to −0.16%; p = 0.04; pint  = 0.02) for SDNN, −5.67% (95% CI: −10.5 to −0.59%; p = 0.03; pint  = 0.04) for HF and −6.64% (95% CI: −10.7 to −2.38%; p = 0.003; pint  = 0.005) for LF. Conclusions: HRV is inversely associated with recent PM air pollution, especially in children with low mtDNAc. Our data revealed that mtDNAc determines susceptibility to adverse autonomic effects of recent PM exposure in children. Highlights: Particulate matter (PM) exposure is associated with lower heart rate variability (HRV). We found an inverse HRV-PM association in children with low mtDNA content. The association was not observed in children with high mtDNA content. Mitochondrial DNA determines susceptibility to adverse autonomic effects of PM.